2015
DOI: 10.3389/fneur.2015.00221
|View full text |Cite
|
Sign up to set email alerts
|

The Complexity of Biomechanics Causing Primary Blast-Induced Traumatic Brain Injury: A Review of Potential Mechanisms

Abstract: Primary blast-induced traumatic brain injury (bTBI) is a prevalent battlefield injury in recent conflicts, yet biomechanical mechanisms of bTBI remain unclear. Elucidating specific biomechanical mechanisms is essential to developing animal models for testing candidate therapies and for improving protective equipment. Three hypothetical mechanisms of primary bTBI have received the most attention. Because translational and rotational head accelerations are primary contributors to TBI from non-penetrating blunt f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
13

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 83 publications
(100 reference statements)
0
34
0
13
Order By: Relevance
“…During deployments, there is a high overlap in blast and blunt-force traumatic brain injuries (TBIs) (Chandra and Sundaramurthy, 2015; Manners et al, 2016), obscuring the physiological impact of isolated blast exposure in humans (Mac Donald et al, 2016b; MacDonald et al, 2014). This is concerning, because in animal model blast-induced TBI (biTBI) has different signature features than blunt-force TBI (Courtney and Courtney, 2015). Previously, we have linked chronic neurological symptoms related to a combination of blast and TBIs in military personnel to greater inflammation, suggesting that inflammation may contribute to blast related pathology, yet no acute clinical studies to understand this relationship have been undertaken (Devoto et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…During deployments, there is a high overlap in blast and blunt-force traumatic brain injuries (TBIs) (Chandra and Sundaramurthy, 2015; Manners et al, 2016), obscuring the physiological impact of isolated blast exposure in humans (Mac Donald et al, 2016b; MacDonald et al, 2014). This is concerning, because in animal model blast-induced TBI (biTBI) has different signature features than blunt-force TBI (Courtney and Courtney, 2015). Previously, we have linked chronic neurological symptoms related to a combination of blast and TBIs in military personnel to greater inflammation, suggesting that inflammation may contribute to blast related pathology, yet no acute clinical studies to understand this relationship have been undertaken (Devoto et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, following a moderate FPI, a mixed model of focal and diffuse injury (Thompson et al , 2005), oligomeric and phosphorylated tau are increased acutely: 4h, 24h and 2 weeks post-injury (Gerson et al , 2016; Hawkins et al , 2013). Mild blast TBI, which encompasses both the blast wave and rotational acceleration-deceleration forces and results in diffuse injury, transient axonal injury, and vascular pathology (Courtney and Courtney, 2015; Kovacs et al , 2014), has also been shown to increase tau acutely following injury. For example, mild blast TBI increases phosphorylated tau in rat hippocampus 6h post-injury (Perez-Polo et al , 2015), and a repetitive blast injury consisting of three closely spaced blasts results in total tau levels being increased 24h post-injury in mouse cerebellum (Arun et al , 2013).…”
Section: Tbi Tau and Cte - The Animal Modelsmentioning
confidence: 99%
“…Among these, primary injury is the most difficult to distinguish due to its co‐occurrence with events that cause overt physical damage (Bhattacharjee, ). Although primary injury is now known to cause neurological impairments in the absence of other modes of injury, it remains the least understood type of injury and has motivated studies focusing on the spectrum of injuries that result from exposure to blast (Courtney & Courtney, ; Elder & Cristian, ; Hicks, Fertig, Desrocher, Koroshetz, & Pancrazio, ; Nakagawa et al, ; Svetlov et al, ).…”
Section: Pathological Mechanisms Underlying Blast Injurymentioning
confidence: 99%
“…Acceleration‐deceleration, direct cranial transmission of the blast wave, and thoracic transmission are the main pathological events attributed to blast exposure (Courtney & Courtney, ; Goldstein et al, ; Gullotti et al, ). Although neural damage due to acceleration‐deceleration from blast waves traversing the skull is an accepted contributor of blast injury, thoracic transmission was initially the most widely cited mechanism.…”
Section: Pathological Mechanisms Underlying Blast Injurymentioning
confidence: 99%